Occupational hazards and health problems among traffic personnel of Mangaluru city - Mishra, Prakash Kumar; Purushothama, Jagannath (International Journal Of Community Medicine And Public Health, 2019)
Background: Occupational health risks and hazards due to the polluted environment have become a serious public health concern. Thus, the duty-bound personnel like traffic police who are continuously exposed, may be at high risk and badly suffer from related health problems. This study was conducted to determine the prevalence of occupational hazards and related health problems among traffic personnel in Mangaluru city. It also aimed to determine the association between occupational hazards and health problems. Methods: This cross-sectional study was conducted among traffic personnel of Mangaluru city. A semi-structured questionnaire with established reliability and validity was used to measure occupational hazards, protective measures, and health problems. Results: The prevalence of respiratory morbidity, eye symptoms, and auditory symptoms was found to be 51.2%, 61.6%, and 47.5% respectively. Respiratory morbidity and duration of use of protective measures against air pollution are found to be significantly associated. The duration of exposure to noise pollution was also significantly associated with the auditory symptoms. Conclusions: Police personnel suffer from significant occupational health problems, due to hazards like air pollution and noise. Necessary protective measures should be taken to ensure the safety of traffic personnel. This study showed an association between occupational hazards and related health problems.